SINTESIS DAN UJI AKTIVITAS SENYAWA 2-BROMO-4,5-DIMETOKSIKALKON TERHDAP SEL KANKER T47D SECARA IN VITRO - Retno Aliyatul Fikroh (Pharmed: Journal of Pharmaceutical Science and Medical Research, 2018)
Synthesis of chalcone derivated has been synthhesized, structurally determined, and the in vitro cytotoxic activityof T47D cell was evaluated. A novel 2-bromo-4,5-dimethoxychalcone was synthesized by Claisen-Schmidt condensation of acetophenone with 6-bromoveratraldehyde. The synthesis of chalcone was carried out by reflux condition (65°C) for 24 hours using ethanol as a solvent and NaOH as a catalyst. The results showed that these coumpoun produced 81% in yield. The purity of synthesized product was determined by Thin Layer Chromatography. Structure identification was performed by FT-IR and 1H dan 13C-NMR spectrometer. In vitro activity test indicated that 2-bromo-4,5-dimethoxychalcone was not active for inhibiting the growth of T47D with IC50 value more than 100 µg/mL.